Effect of foliar applications of urea, ethanol and putrecine on growth and yield of lettuce (Lactuca sativa) - GUVENC, I; KARATAS, A; KAYMAK, H C (The Indian Journal of Agricultural Sciences, 2011)
The experiment was conducted during 2001-Q2 to find out the effect of urea, ethanol and putrecine on growth and yield of lettuce (Lactuca sativa L.).. The plants were sprayed with urea, ethanol and putrecine. Foliar application consisted of0.6% of urea, 20 and 40% (v/v) ofethanol and 150,350 and 450 ppm of putrecine and sprayed between 4 pm-5pm in a day using a hand sprayer. First application was made at 5-6 true leaves stage later, starting 2nd week after transplantation on 10 May 2001 and 2002. Spray volume used in applications varied from ISO to 250 ml/12 plants. Plants received 4 applications at 7-day intervals during the growing season. Foliar sprays were influenced significantly size of head of lettuce. Dry weight of leaves and root were not affected significantly by foliar treatment of urea, ethanol and putrecine. Putrecine and ethanol applied as a foliar treatment was less effective than urea on lettuce. Foliar fertilization ofurea (0.6 %) as nitrogen sources could be suggested to have better yield and growing properties in lettuce production.